Experimental Calibration of Parameters of Discrete Element Model for Ginkgo Nut - Minji Liu; Jiannan Wang; Zhaoyan You; Yanghua Wu; Ni Wang; Huanxiong Xie (BioResources)
In order to ensure the reliability of the simulation test on the shelling process of ginkgo nuts, the physical parameters (characteristic dimensions, thousand grain mass, moisture content, density, Poisson’s ratio, elastic modulus, and shear modulus), contact parameters (restitution coefficient, static friction coefficient, and dynamic friction coefficient) and actual stacking angle of the ginkgo nuts were measured by physical test methods. A stacking angle test model was established, and simulation tests were performed. Parameter intervals for the simulation were selected according to the measured parameters. Three factors affecting the stacking angle significantly were determined using the Plackett–Burman test: static and dynamic friction coefficients of ginkgo nut–ginkgo nut and the restitution coefficient of the ginkgo nut–steel plate. Each factor’s range was selected using the steepest climbing test. A quadratic polynomial regression model of the stacking angle considering these factors was obtained using the Box–Behnken test. Taking the actual stacking angle of 39.59° as the optimization objective, the optimal combination was formed: the static and dynamic friction coefficients were 0.5 and 0.36, respectively, and the restitution coefficient was 0.42. This combination was used for the verification test. The stacking angle was found to be 41.12°. The relative error was 3.86%, indicating that the model is reliable and can provide a useful reference for relevant research.